Identification of clay minerals of the eastern southern region of Lake Victoria by ethylene glycol and heat: X-ray diffraction and infrared spectroscopy studies - Lugwisha, E. H. J. (Tanzania Journal of Science, 2021)
The effect of glycol and heat on some clay minerals of the eastern southern region of Lake Victoria in Tanzania has been studied. First, Whole Rock Powder mount XRD analysis was carried out at the measuring range 2 # ranging between 2o – 65o. Four non-clay minerals found in samples were Na-feldspar, K-feldspar, pyrope and quartz. Oriented clay mineral XRD analysis diffractograms were developed when the air-dried samples were diffracted in measuring range 2# between 2oo – 32o. Main clay mineral groups found in the samples were kaolinite, illite and montmorillonite. After glycolating the samples, it was evident that kaolinite diffractograms were inverted while montmorillonite diffractograms peaks were widened and shifted. But on heating to 550oC, the peaks for both kaolinite and montmorillonite collapsed. The case was different for illite peaks which showed stability under both treatments. This analysis made it possible to differentiate between kaolinitic and non-kaolinitic clays. IR spectroscopy study was also carried out and the results were presented for comparison to clay minerals identified by XRD analysis. XRD analysis identified kaolinite, illite and montmorillonite as clay minerals in the samples, results which agree with IR. IR absorption bands occurred at 3694, 3825, 694 and ca 430 – 470 cm-1 are characteristic of kaolinite mineral. While absorption bands which appeared at 3455, 3463, 3600, 3440, 3610 and 532 – 539 cm-1 are characteristics of illite mineral group, and a band at 3432 cm-1 signifies the presence of both kaolinite and montmorillonite.